Industrial training report: Malaysian Communications and Multimedia Commission (Selangor) / Muhammad Danial Mohd Khalil - Mohd Khalil, Muhammad Danial (Perpustakaan Tengku Anis, 2016)
Trainee are undergoing the industrial training as the requirement from the university. Training starts in 1st august until 31st December 2016 and trainee are being place at the Talent Management Department under the Human Capital Management and Competency Division. During the five month at Malaysian Communications and Multimedia Commission there are many input that trainee get from the training that give trainee more exposure in the communication and multimedia in this country. Meanwhile trainee also learn a new knowledge such as human resources management, communication skill, and many more. The contribution trainee towards the organization is trainee was develop a system for assist the recruitment team. Trainee develop the Career Fair System. a new system that can assist the recruitment team in order to making the decision for the recruitment and selection process.